Decision-making training in sporting officials: Past, present and future. (September 2021) - Kittel, Aden; Cunningham, Ian; Larkin, Paul; Hawkey, Matthew; Rix-Lièvre, Geraldine
Abstract: Objective: Decision-making has commonly been cited as the most important skill for successful performance in sports officials, however insight into how this critical skill is improved through off-field training has lagged. The overall aim of this paper is to provide a narrative review concerning the evolution of off-field decision-making training approaches in interactor sporting officials (i.e., those with high movement and perceptual demands). This paper will reconcile these past forms of training with theories and concepts discussed in the officiating and sporting literature, with subsequent recommendations for future investigations. Design: Narrative review. Method: 10 peer-reviewed studies on the development of decision-making in interactor sporting officials were comprehensively scrutinized. Results: Decision-making training studies were found to use diverse methodological approaches and theoretical perspectives. There are several limitations in the decision-making training literature for officials, such as limited representativeness in training, leading to a more decontextualized approach. Conclusions: Future studies should consider stronger representativeness by including more competition constraints into training decision-making, such as contextual factors. Reflective training and individualized approaches may be an appropriate training methodology to train officials for adequacy, rather than accuracy. Highlights: Video-based training is a common method to develop decision-making skill in sports officials. Theoretical frameworks should be considered for future training design. Specifically, representative design implies more in-game constraints should be incorporated to off-field training.